Fixed Point Theorems for Fuzzy $(γ,β)$-Contractions in non-Archimedean Fuzzy Metric Spaces - Muzeyyen Sangurlu Sezen (Sahand Communications in Mathematical Analysis, 2021)
In this paper, we introduce new concepts of fuzzy $(γ,β )$-contraction and prove some fixed point results for fuzzy $(γ,β )$-contractions in complete non-Archimedean fuzzy metric spaces. Later, we define a fuzzy $(γ,β )$-weak contraction and establish some new fixed point results for fuzzy $(γ,β )$-weak contractions. Also, some examples are supplied in order to support the useability of ourresults.